2017
DOI: 10.1177/2333393617691860
|View full text |Cite
|
Sign up to set email alerts
|

Making It All Work

Abstract: The greater prevalence of type 2 diabetes is a critical issue among the U.S. Hispanic population. This study examined the struggles of Hispanic adults managing type 2 diabetes with limited resources. Ten Hispanic adults (enrolled in a larger study to determine the effects of diabetes self-management intervention), 25 to 80 years of age and living in a rural West Texas county in the United States, were selected. Three categories of challenges emerged: (a) diabetes self-care behaviors and challenges, (b) challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
0
0
Order By: Relevance
“…Family roles in this review were affected by a lack of appropriate formal and informal support systems and a scarcity of resources. The findings of this review are similar to Thomas et al (2017) study, which found that multifactorial events at personal, familial and social levels affected adults with DM2's experiences, including the challenge of adopting DSMP in everyday life, the struggle with limited resources including income, employment, healthcare resources, knowledge regarding DM2 and healthcare dynamics and the need for support from their families and faith communities. Hence, Vanstone et al (2017) used socioecological theory to explain how one level of support can influence the next level and how these interweaved to influence adults with DM2 and their families' experiences.…”
Section: Discussionsupporting
confidence: 85%
“…Family roles in this review were affected by a lack of appropriate formal and informal support systems and a scarcity of resources. The findings of this review are similar to Thomas et al (2017) study, which found that multifactorial events at personal, familial and social levels affected adults with DM2's experiences, including the challenge of adopting DSMP in everyday life, the struggle with limited resources including income, employment, healthcare resources, knowledge regarding DM2 and healthcare dynamics and the need for support from their families and faith communities. Hence, Vanstone et al (2017) used socioecological theory to explain how one level of support can influence the next level and how these interweaved to influence adults with DM2 and their families' experiences.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, as compared to non-Hispanic Whites, Hispanic patients are more likely to demonstrate medication nonadherence [ 18 ] and less likely to fill prescriptions [ 19 ]. It has been postulated that inadequate access to care [ 20 ], patient-physician language barriers [ 21 ], prohibitive costs [ 22 , 23 ], and distrust of the healthcare system contribute to treatment inequities among the Hispanic population. However, irrespective of the underlying causes, inadequate treatment in the setting of nonadherence can have a devastating effect on health outcomes.…”
Section: Discussionmentioning
confidence: 99%